DEVELOPMENT OF RUMAH ADIKSIMBA : A GAME-BASED LEARNING MEDIA TO ENHANCE STUDENTS’ UNDERSTANDING OF INTERROGATIVE WORDS - Niken Nastiti; Agus Yuwono; Panca Dewi Purwati (Universitas Majalengka, 2025)
The low understanding of grade IV elementary school students of interrogative sentences shows the need for innovation in Indonesian language learning. This study aims to develop interactive media Rumah Adiksimba assisted by a game based learning approach to improve students’ understanding of the use of interrogative words. The research uses the ADDIE model development method which includes the stages of needs analysis, media design, prototype development, limited implementation, and effectiveness evaluation. Media validation was conducted by material and media experts, while the effectiveness test was conducted on 29 fourth grade students of SDN 1 Singorojo. The validation results showed that the media was very feasible to use with scores above 85% in all aspects. The trial showed a significant increase in learning outcomes, with the average score increasing from 58.62 (pretest) to 83.76 (posttest). In addition, students showed active engagement and positive responses to the media. This media also encourages students’ ability to analyze, assess, and develop interrogative sentences contextually. This finding reinforces the effectiveness of the game-based learning approach in enhancing the understanding of interrogative words in Indonesian language learning at the elementary school level.